Trans-Iliac Aortic Valve Replacement: Feasibility, Safety, and Medium-Term Follow-up. (May 2019) - Gennari, Marco; Trabattoni, Piero; Pepi, Mauro; Polvani, Gianluca; Salvi, Luca; Agrifoglio, Marco
Background: Transcatheter aortic valve replacement (TAVR) is nowadays generally accepted as the treatment of choice for high- to intermediate-risk patients with severe aortic stenosis not suitable for the standard surgical replacement. Many vascular accesses have been described for the valve delivery, comprising the common iliac artery as the arterial site of access. Methods: From September 2008 to June 2014, 440 patients underwent TAVR at our institution. We report a series of 12 patients that have undergone TAVR via a trans-iliac (TI) retroperitoneal surgical approach and also discuss its feasibility, security, and medium-term follow-up. Results: The 30-day survival rate was 92%. Only 1 local vascular access major complication occurred requiring an iliac-femoral bypass grafting with a vascular graft. Two patients experienced transient neurological ischemic attack. At 3-year follow-up, all the 11 patients were alive and well and the echocardiographic evaluation revealed good function of the prosthesis. Conclusions: The TI route seems to be feasible with a low profile of local complications. It may be a reasonable access alternative to the femoral artery and to the trans-apical approach. A broader, prospective study is advisable to gain general consensus on this approach.